The effect of pressure on the electronic properties of diamond crystal - Sajjad Nadhim Naeem Khalil; Ahmed Shaker Mahmoud Hassoun; Murtdha Kareem Ghasim Habib; Sami Najah Abbas Kati AlBandar; Sarah Hamid Aifan Farhan (Genius Journals, 2024)
The study included the application of quantum mechanical calculations using the average neglect method of differential interference to the effect of pressure (pinch or pull stress) on the electronic properties and the extent of its effect on both the valence band width, the conduction band width, the lattice constant of the crystal, as well as the energy gap and the relationship of pressing and pulling stress with ductility, as follows :Increasing the width of both the valence and conduction bands and decreasing the energy gap in the pressing stress.
Keywords: pressure; properties; diamond crystal